The Impact of Supplementation With Whey Protein Isolate and/or Omega-3 Fatty Acids on Sleep and Mood in Postmenopausal Women (SHAPE Study). (7th June 2021) - Hawley, Aubree; Baughn, Caroline; Tacinelli, Angela; Walker, Sam; Liang, Xinya; Gbur, Ed; Baum, Jamie
Abstract: Objectives: Approximately 30% of adults ≥ 50 years of age suffer from poor sleep quality and the prevalence of sleep disruption is notably higher in postmenopausal women, with 35 to 60% reporting significant sleep disruption.  Sleep deprivation and low sleep quality are associated with increased energy intake, insulin resistance, elevated glucose, and mood disturbances (e.g., stress, cortisol, and depression). The objective of this study was to determine if the effect of protein and/or omega-3 fatty acid (O3FA) supplementation improves mood and sleep in postmenopausal women. Methods: Thirty-nine postmenopausal women (age: 61.3 ± 8.7 years; BMI: 27.6 ± 6.6 kg/m 2 ) were randomly allocated to one of 5 groups: 1) control (CON; no intervention free-living; n = 6), 2) whey protein isolate (PRO; 25 g/d; n = 7), 3) O3FA (DHA/EPA; 4.3 g/d; n = 10), 4) PRO + placebo soybean oil (PRO + PLA; 4.1 g/d; n = 7), or 5) PRO + O3FA (n = 9). Sleep and mood states were assessed at 0, 4, 8, 12, and 16 weeks, except objective sleep, which was assessed at 0, 8, and 16 weeks.  Sleep was measured using the Pittsburgh Sleep quality Index (PSQI) and wrist actigraphy, mood was measured using the Profile of Mood States (POMS), and markers of sleep and mood, orexin, BDNF, and cortisol, were measured using commercially available kits. Results: A significant time effect (P < 0.05) was observed on subjective sleep (PSQI), subjective mood states, BDNF, and cortisol concentrations. Although not significant, a greater % decrease in PSQI Global Sleep Score was observed in PRO (-30.3%), O3FA (-23.3%), PRO + PLA (−20.2%), and PRO + O3FA (−26.4%) when compared to an increase in CON (+18%). Similarly, a decrease trend in POMS Total Mood Disturbances from baseline was observed in PRO (−10 ± 27.7), O3FA (−6.7 ± 18.2), and PRO + O3FA (−6.9 ± 27.7) compared to no change in PRO + PLA (0.1 ± 11.5) and an increase in CON (5 ± 15.8). We observed a significant treatment effect on orexin (OXA; pg/mL; P < 0.05). OXA increased significantly in PRO + O3FA compared to all other groups ( P < 0.05). Conclusions: Although not significant, the data suggests individual and combined supplementation of protein and O3FA have the potential to improve sleep, mood, and orexin levels in postmenopausal women. NCT0303041 Funding Sources: Arkansas Biosciences Institute